ANALISIS KINERJA KEUANGAN DITINJAU DARI RASIO SOLVABILITAS, AKTIVITAS DAN PROFITABILITAS PT AKASHA WIRA INTERNASIONAL Tbk - Syahnor1, Urip Gunawan (EKONOMIA, 2018)
Urip Gunawan Syahnor 2018. Faculty of Economics, University August 17, 1945 Samarinda. Financial Performance Analysis Judging from the Solvency, Activity and Profitability Ratios of PT Akasha Wira Internasional Tbk Period 2014 - 2107. Under the guidance of mother Elfreda Aplonia as supervisor I and Mr. H. Sunarto as mentor II.                The background of this research is tight business competition along with the development of the economy resulting in demands for the company to continue to develop innovation, improve its performance, and expand its business in order to continue to survive and compete. This study aims to determine the decline in terms of solvency ratios measured by debt to equity ratio, activity ratio measured by total assets turnover, and profitability ratios measured from net profit margins from 2014 to 2017.                The basic theory of this research is that financial management which focuses on each solvency ratio is measured by the debt to equity ratio, the activity ratio is measured by total assets turnover, and the profitability ratio is measured by the net profit margin. The analytical  tool used is each solvency ratio measured by the debt to equity ratio, the activity ratio measured by total assets turnover, and the profitability ratio measured by the net profit margin ..                The data required is 4 years, namely in 2014 to 2017 which is obtained from the Indonesian stock exchange. The results of this study indicate: 1) the debt to equity ratio has increased in 2014-2015, and experienced a decline in 2015-2016 until 2016-2017. 2) total assets turnover has decreased in 2014, 2015 and 2016. 3) net profit margin experienced an increase in 2014-2015, and decreased 2015-2016 until 2016-2017.                The conclusion of the hypothesis of this study was measured from 1) debt to equity ratio based on the calculation results fluctuated then this hypothesis was rejected, 2) the total asset turnover based on the calculation results fluctuated then this hypothesis was rejected, 3) the net profit margin based on the calculation results fluctuated then the hypothesis this is reject.